HUBUNGAN JENIS PERSALINAN DENGAN KEJADIAN ASFIKSIA NEONATORUM - Rahayu, Theresia Asmaningsih Retno; Santoso, Sabar; Hernayanti, Munica Rita (Jurnal Kesehatan Ibu dan Anak, 2015)
The incidence rate of neonatal asphyxia in Kulon Progo Regency Hospital has increased between 2011 to 2012. 35.6% in 2011 to 38.5% in 2012. The act of childbirth in hospitals also increased between 2011 (48.5%) to 2012 (50.3%). Research to determine the ype of labor relationship with the incidence of neonatal asphyxia in Kulon Progo district hospitals in 2012. This is a type of observational analytic study using a case-kontroi study design (retrospective). Subjects were Babies born Apgar <7 and ? APGAR 7.Total baes born with a sample of 100 cases and 100 kontrots. asphyxia dependent variable and the independent variable types delivery. The analysis used Chi-squarewith significance level 0.05. Risk Estimate and test (OR). The results of Chi-Square test witha value of 0.05 obtained value p = 0.000, which means there is a significant relationship between the type of delivery with the ncidence of neonatal asphyxia. OR calculation results showed amean value of 3.79 Babies born with artificial birth had 3.79 times greater risk than the Babies born with spontaneous labor. There is significant correlation between the type of delivery with the incidence of neonatal asphyxia in Kulon Progo district hospitals in 2012. Babies born through artificial birth asphyxia have likely experienced 3,79 times greater than infants born spontaneously.